Pengaruh Standar Operasional Prosedur terhadap Kinerja Pegawai pada BPKD Aceh Barat - Eti Yuliana; Mahrizal Mahrizal (Universitas Kristen Indonesia Toraja, 2024)
This study aims to explore the impact of the Standard Operating Procedures (SOP) on employee performance at the West Aceh Regional Financial and Asset Management Agency (BPKD). The research sample consisted of 85 BPKD Aceh Barat employees who were selected using a purposive sampling technique. Data was collected through a questionnaire that had been tested for validity and reliability. Data analysis was performed using simple linear regression and the SPSS program. The results showed that SOP had a positive and significant impact on the performance of BPKD Aceh Barat employees. The value of t count is 5.015 and t table for this study is 2.00, indicating that t count is greater than t table. Thus, it can be concluded that SOPs have a significant influence on employee performance at BPKD Aceh Barat.